Alone with One's Thoughts: Wittgenstein on Philosophical Thinking in Isolation - Jack Manzi (Janeway JS, 2021)
This paper explores the relationship between isolation and philosophical thinking by exploring Wittgenstein’s own experiences of isolation and how they intersect with key themes in his philosophical work. In particular, I explore the relationship between isolation, honesty, and one of the central problems posed in Wittgenstein’s later work: the problem of dogmatism. I conclude with some observations about how Wittgenstein’s experiences of isolation might be considered to be ‘liberatory’ experience.